Study into conditions for the interaction between different types of transport at intermodal terminals - Petrushov, Vasyl; Shander, Oleg (Eastern-European Journal of Enterprise Technologies, 2018)
The study conducted into organization of the interaction among various types of transport at intermodal terminals found that it is necessary to improve the technological process of a terminal to achieve effective functioning of transshipment terminals. Specifically, it is necessary to provide basic requirements, such as continuity, rhythm, parallelism and sequenced-flow of all operations and maximum combination with the high quality of unconditional use. The study proved that achievement of appropriate conditions is possible when using the descriptive model of a two-port terminal. It operates due to the processes of self-synchronization of movement of automated platforms, which transport containers between a road portal and a railroad portal. The study established that we must solve the design problem of creation of perfect computer models for needs of organization of the interaction of various types of transport at intermodal terminals in a combination of descriptive model and analytical model. These models include software components and hardware components that provide conditions for implementation of the concept of self-synchronization movement of forklift trucks. Specifically, the study found that the self-timed control approach provides a greater degree of coordination in operation of a container terminal. That makes it possible to improve the parallelism of processes, that is, simultaneous implementation of events within a system. The study showed a possibility for the formalization of processes of self-synchronization by means of Petri nets. This mathematical apparatus is very convenient for modeling dynamic discrete systems and makes it possible to explore the sequential execution of all processes, which occur at an intermodal terminal. Based on the simulation, the study proved that an average container demurrage at a terminal diminishes, which makes it possible to increase processing capacity and to reduce unit costs for processing a container at a terminal. Thus, there is reason to state that it is quite possible to develop technologically complete "seaport-railroad portal-automobile portal" terminal structures in various configurations. The type of configuration depends on selected logistics routes for delivery of good. We should apply the method of organization of operation of a two-port terminal for this purpose.